The Effect of Fiber Sizes on Mechanical Properties of Millet Husk (Pennisetum glaucum) Fiber Filled High Density Polyethylene Composites - Hammajam, A. A.; Nur, I. Z.; Salit, S. M.; Zulkeffle, L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study examined the effect of fiber sizes on the mechanical properties of millet husk powder (MHP) filled high density polyethylene (HDPE) thermoplastic composites. The MHP-HDPE composites were prepared by melt blending techniques, accompanied by compression molding process. Three different fiber sizes; 250µm, 500µm and 750µm were pulverized and the fiber loading was 10%, 20% 30% and 40% by weight. Tensile and impact properties were tested using universal testing machine (UTM). 1The results show that ensile strength increased at certain loadings while tensile modulus increased by increasing the millet fiber loading. While the impact strength decreases substantially with increase fiber loading the tensile strain considerably decreased at millet husk fiber application above 10%. Therefore, it was observed that composites with least size fiber indicated improvement with increasing strength as well as relative extension.